Multi-scale biomarker evaluation of the toxicity of a commercial azo dye (Disperse Red 1) in an animal model, the freshwater cnidarian Hydra attenuata. (1st June 2016) - de Jong, Laetitia; Pech, Nicolas; de Aragão Umbuzeiro, Gisela; Moreau, Xavier
Abstract: Acute (24 h, 48 h, 72 h) and chronic (7 days) tests have been performed to evaluate the effects of the commercial azo dye Disperse Red 1 (DR1) using various biomarkers in the freshwater invertebrate Hydra attenuata . Morphological changes have been selected to calculate ecotoxicological thresholds for sublethal and lethal DR1 concentrations. A multinomial logistic model showed that the probability of each morphological stage occurrence was function of concentration, time and interaction between both. Results of oxidative balance parameter measurements (72 h and 7 days) suggest that polyps set up defense mechanisms to limit lipid peroxidation caused by DR1. DR1 exposure at hormetic concentrations induces increase of asexual reproductive rates. This result suggests (1) an impact on the fitness-related phenotypical traits and (2) trade-offs between reproduction and maintenance to allow the population to survive harsher conditions. Changes in serotonin immuno-labeling in polyps showing alterations in feeding behavior suggest that chronic DR1 exposure impaired neuronal processes related to ingesting behavior in H. attenuata . This ecotoxicity study sheds light on the possible serotonin function in Hydra model and reports for the first time that serotonin could play a significant role in feeding behavior. This study used a multi-scale biomarker approach investigating biochemical, morphological, reproductive and behavioral endpoints in Hydra attenuata. This organism is proposed for a pertinent animal model to assess ecotoxicological impact of pollutant mixtures in freshwater environment. Graphical abstract: Highlights: Morphological changes in Hydra attenuata exposed to commercial azo dye (DR1) depend on concentration, time and both parameters. Polyps set up defense mechanisms to limit lipid peroxidation caused by DR1. Hormetic concentrations stimulate asexual reproduction allowing population survival. Decreased 5-HT expression is observed in exposed polyps showing impaired feeding behavior.